Reconstitution of synaptic Ion channels from rodent and human brain in Xenopus oocytes: a biochemical and electrophysiological characterization. Issue 3 (13th June 2016) - Mazzo, Francesca; Zwart, Ruud; Serratto, Giulia Maia; Gardinier, Kevin M.; Porter, Warren; Reel, Jon; Maraula, Giovanna; Sher, Emanuele
Abstract : Disruption in the expression and function of synaptic ion channels is critical in the pathophysiology of human neurodegenerative diseases. We here show that synaptosomes purified from rodent and human frozen brain (control and Alzheimer disease) can be studied both biochemically and functionally. This method opens the way to directly testing the effects of novel drugs on native ion channels. Abstract: Disruption in the expression and function of synaptic proteins, and ion channels in particular, is critical in the pathophysiology of human neuropsychiatric and neurodegenerative diseases. However, very little is known regarding the functional and pharmacological properties of native synaptic human ion channels, and their potential changes in pathological conditions. Recently, an electrophysiological technique has been enabled for studying the functional and pharmacological properties of ion channels present in crude membrane preparation obtained from post‐mortem frozen brains. We here extend these studies by showing that human synaptic ion channels also can be studied in this way. Synaptosomes purified from different regions of rodent and human brain (control and Alzheimer's) were characterized biochemically for enrichment of synaptic proteins, and expression of ion channel subunits. The same synaptosomes were also reconstituted in Xenopus oocytes, in which the functional and pharmacological properties of the native synaptic ion channels were characterized using the voltage clamp technique. We show that we can detect GABA, (RS)‐α‐Amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid, and NMDA receptors, and modulate them pharmacologically with selective agonists, antagonists, and allosteric modulators. Furthermore, changes in ion channel expression and function were detected in synaptic membranes from Alzheimer's brains. Our present results demonstrate the possibility to investigate synaptic ion channels from healthy and pathological brains. This method of synaptosomes preparation and injection into oocytes is a significant improvement over the earlier method. It opens the way to directly testing, on native ion channels, the effects of novel drugs aimed at modulating important classes of synaptic targets. Disruption in the expression and function of synaptic ion channels is critical in the pathophysiology of human neurodegenerative diseases. We here show that synaptosomes purified from rodent and human frozen brain (control and Alzheimer disease) can be studied both biochemically and functionally. This method opens the way to directly testing the effects of novel drugs on native ion channels.